Molecular Detection of Resistance To Bacterial Leaf Blight on Conde Indonesian Rice Variety - Fatimah, Fatimah; Prasetiyono, Joko; Polosoro, Aqwin; Baroya, Mushlihatun (ANNALES BOGORIENSES, 2018)
Rice bacterial leaf blight (BLB) disease caused by Xanthomonas oryzae pv. oryzae (Xoo) affected grain yield and decreasing rice production in rice growing countries. Conde, Indonesian rice variety, exhibits high resistance to most of the Indonesian races of (BLB) and has been used in Indonesia for cultivated rice. This study was aimed to conduct the molecular detection between proximal markers in chromosome 6 and relative expression of Conde rice variety compare to IRBB7 in Xa7 region. The population screening, BLB evaluation and molecular detection around the Xa7 region were conducted. The results showed from the collection of individual recombinants between resistant and susceptible parents narrow the region containing the BTBPOZ domain. The sequence alignment of Xa7LD37 in two resistant and three susceptible cultivars demonstrated a perfect association. The sequence alignment in exon region of Loc_Os06g46240 in Nipponbare, IRBB7, and IR64 identified indel/SNPs in this region leading to nucleotide substitution and frameshift resulting in amino acid change between resistant and susceptible cultivars. It was predicted that Conde revealed the similar gene action with Xa7 gene for BLB that encodes a BTB POZ domain.